Evaluasi Tingkat Keterpakaian Koleksi Perpustakaan Majelis Ulama Indonesia Sumatera Utara - Dea Amanda; Sori Monang; Muslih Fathurrahman (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Research entitled "Evaluation of Collection Utilization Level at the Library of the Majelis Ulama Indonesia in North Sumatra." The main issue addressed in this thesis is the level of collection utilization at the Library of the Majelis Ulama Indonesia in North Sumatra. This study aims to evaluate the level of collection utilization at the library. The research method used is quantitative with a descriptive approach. Data collection techniques include surveys and documentation. Data processing uses descriptive quantitative analysis using frequency and percentage. The collected data are tested for validity and reliability using IBM SPSS v23 software. The results and discussion of this study show that the average perception score of library users is 81.85%, indicating a positive perception of collection utilization. However, efforts are needed from the library to improve or expand its collection, so that collection utilization can increase and gain better perception in the future.